2022
DOI: 10.3389/fcvm.2022.851419
|View full text |Cite
|
Sign up to set email alerts
|

Pak2 Regulation of Nrf2 Serves as a Novel Signaling Nexus Linking ER Stress Response and Oxidative Stress in the Heart

Abstract: Endoplasmic Reticulum (ER) stress and oxidative stress have been highly implicated in the pathogenesis of cardiac hypertrophy and heart failure (HF). However, the mechanisms involved in the interplay between these processes in the heart are not fully understood. The present study sought to determine a causative link between Pak2-dependent UPR activation and oxidative stress via Nrf2 regulation under pathological ER stress. We report that sustained ER stress and Pak2 deletion in cardiomyocytes enhance Nrf2 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Additionally, NO produced by endothelial NO synthase (eNOS) plays a role in the regulation of cell growth, apoptosis, and tissue perfusion (Dimmeler et al ., 1997) and our findings of apoptosis and downregulation of NOS corroborates early findings (Feng et al ., 2002). ER stress and oxidative stress have been highly implicated in many cardiac pathologies (Binder et al ., 2022) (Dhalla et al ., 2000) including the pathogenesis of AF (Li et al ., 2010). Recent studies highlight the importance of PAK2.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NO produced by endothelial NO synthase (eNOS) plays a role in the regulation of cell growth, apoptosis, and tissue perfusion (Dimmeler et al ., 1997) and our findings of apoptosis and downregulation of NOS corroborates early findings (Feng et al ., 2002). ER stress and oxidative stress have been highly implicated in many cardiac pathologies (Binder et al ., 2022) (Dhalla et al ., 2000) including the pathogenesis of AF (Li et al ., 2010). Recent studies highlight the importance of PAK2.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of NVS-PAK1-1 on solid cancers in preclinical models is yet to be conducted. A recent study by Genentech suggested that the toxicity of group-I PAK inhibitors may be associated with the inhibition of PAK2 [ 240 ], which is an advantage for NVS-PAK1-1 over all other known PAK inhibitors. Unfortunately, PAK2 is expressed and activated in most cancers, which creates questions about the suitability of NVS-PAK-1-1 as a cancer therapeutic.…”
Section: Inhibitors Of Paks and Their Potential Clinical Utilitymentioning
confidence: 99%
“…However, the ubiquitin E3 ligase TRIM21 suppressed the p62-Keap1-Nrf2 antioxidant pathway in a doxorubicin-induced cardiac dysfunction model, and Trim21 knockout mice were protected from HF [ 96 ]. P21-activated kinase 2 (PAK2) targets Nrf2/Keap1 ubiquitination by mediating 3-hydroxy-3-methylglutaryl reductase degradation 1 (HRD1) expression, thereby alleviating detrimental ER stress and HF, offering another potential therapeutic strategy for HF [ 97 ]. Moreover, in a rat model of chronic HF, miR-129-5p was found to target Smad ubiquitin regulatory factor 1 (SMURF1) and repress the ubiquitination of PTEN to improve cardiac function [ 98 ].…”
Section: Interaction Of the Ups And Oxidative Stress In Cvdsmentioning
confidence: 99%